CAUSALITY BETWEEN EXCHANGE RATE AND ECONOMIC GROWTH IN BANGLADESH - Kazi Mohammed Kamal Uddin; Mohammad Morshedur Rahman; G. M. Azmal Ali Quaosar (European Scientific Journal, ESJ, 2014)
This paper attempts to examine the relationship between Exchange Rate (ER) and Economic Growth (EG) proxied by Real Gross Domestic Product (RGDP) in Bangladesh for a period of 41 years ranges from 1973 to 2013 by using time series econometric technique. The empirical results show that there is a significant positive correlation between ER and EG. The results also advocate the presence of long-run equilibrium relationship between ER and EG. This is evidenced from Granger’s Causality Test that there is a bi-directional causality runs through ER to EG and EG to ER.